2010
DOI: 10.1111/j.1475-6773.2010.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Job Stress and Job Satisfaction: Home Care Workers in a Consumer‐Directed Model of Care

Abstract: Objective. To investigate determinants of job satisfaction among home care workers in a consumer‐directed model. Data Sources/Setting. Analysis of data collected from telephone interviews with 1,614 Los Angeles home care workers on the state payroll in 2003. Data Collection and Analysis. Multivariate logistic regression analysis was used to determine the odds of job satisfaction using job stress model domains of demands, control, and support. Principal Findings. Abuse from consumers, unpaid overtime hours,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
117
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 27 publications
15
117
0
1
Order By: Relevance
“…Our findings about social support reinforce reports by others that formal training that fosters the working relationship between the provider and the recipient may be beneficial (Baron & Habes, 2004;Delp et al, 2010;Menne et al, 2007). Examples of such training might include sections on communication, role negotiation, conflict resolution, and assertiveness (Baron & Habes, 2004;Menne et al, 2007).…”
Section: Temporal Factorssupporting
confidence: 84%
See 1 more Smart Citation
“…Our findings about social support reinforce reports by others that formal training that fosters the working relationship between the provider and the recipient may be beneficial (Baron & Habes, 2004;Delp et al, 2010;Menne et al, 2007). Examples of such training might include sections on communication, role negotiation, conflict resolution, and assertiveness (Baron & Habes, 2004;Menne et al, 2007).…”
Section: Temporal Factorssupporting
confidence: 84%
“…The alternative, that painful WRMSDs reduce social support is possible, but logically less likely. Social support from work peers, friends, and the spouse of the home care provider has previously been associated with lower work stress, better health, and higher job satisfaction (Delp et al, 2010;Denton et al, 2002). To our knowledge, however, so-cial support from the care recipient has not been quantitatively investigated for its impact on PAS provider reports of injury or MSD symptoms.…”
Section: Temporal Factorsmentioning
confidence: 94%
“…Immigrant employees who were housekeepers in the U.S.A. found that job characteristics, organisation, social support, social economic status, low education and occupation characteristics influenced their job pleasure and mental health problems [16][17][18]. This was similar to a study done in China, and Chinese immigrant employees who worked in Canada, which found that working hours, income, family support, housing conditions, age, job characteristics, income, and social support related to mental health [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Yet, little is known about whether or how an IHSS program could support home assessment of common symptoms. To our knowledge, no prior study has explored the use of IHSS programs to assess symptoms for vulnerable older adults.…”
mentioning
confidence: 99%
“…Lack of confidence in addressing symptoms and insufficient training are sources of stress for in-home care workers. 6,25,39 Addressing these concerns could benefit IHSS providers as studies show that self-confidence and training improve job satisfaction and retention of home health workers; crucial for this workforce and the elderly population. 40,41 IHSS symptom assessment may also act as a bridge for consumers to primary care and palliative care services.…”
mentioning
confidence: 99%